Synthesis of novel 6-substituted-5,6-Dihydrobenzo[4,5] Imidazo[1,2-c] quinazoline compounds and evaluation of their properties - Hasan, HA; Abdulmalek, E; Saleh, TA; Rahman, MBA; Shaari, KB; Yamin, BM; Chan, KW (Elsevier Science BV, 2024)
Indexed by WOS